Catechol-O-methyltransferase polymorphism Val158Met is associated with distal neuropathic pain in HIV-associated sensory neuropathy. (1st August 2019) - Xu, Jennie; Umlauf, Anya; Letendre, Scott; Franklin, Donald; Bush, William S.; Atkinson, Joseph H.; Keltner, John; Ellis, Ronald J.
Abstract : Background: Many of those aging with HIV suffer from distal neuropathic pain (DNP) due to HIV-associated sensory neuropathy (HIV-SN). Prior studies have linked chronic pain conditions to a variant of the catechol- O -methyltransferase (COMT), Val 158 Met. This variant confers reduced enzymatic activity and results in higher synaptic dopamine levels. Here we examined the role of Val 158 Met as a predictor of DNP in HIV-SN. Methods: In 1044 HIV-infected individuals enrolled in CNS HIV Antiretroviral Therapy Effects Research, an observational study across six US institutions, we characterized the relationship between Val 158 Met and DNP in HIV-SN. Participants underwent neurologic examination and genotyping. Stratification into genetic ancestry groups was employed to eliminate bias due to genetic background. Findings: Of 590 participants with HIV-SN, 38% endorsed DNP, 24% reported nonpainful symptoms of neuropathy (paresthesia and numbness), and 38% were asymptomatic. Compared with asymptomatic HIV-SN, Val 158 Met was associated with 2.3 higher odds of DNP. There were no increased odds of nonpainful symptoms. The association remained significant after controlling for other risk factors for DNP: lifetime diagnosis of depression, older age, ancestry, cumulative exposure to dideoxynucleoside antiretrovirals, diabetes, and nadir CD4 + . Stratified by genetic ancestry, the association between Val 158 Met and DNP was significant in European and African genetic ancestry. Interpretation: Val 158 Met may be a genetic marker for susceptibility to DNP in HIV-SN. Our findings support the notion that differences in pain processing mediated by COMT-related dopamine signaling play a role in susceptibility to DNP in HIV-SN. Because prior studies suggest that the COMT allele may influence dose-response relationships with opioid treatment, knowing COMT genotype could influence management.